2018
DOI: 10.1093/cercor/bhy258
|View full text |Cite
|
Sign up to set email alerts
|

Neural stem cell lineage-specific cannabinoid type-1 receptor regulates neurogenesis and plasticity in the adult mouse hippocampus

Abstract: Neural stem cells (NSCs) in the adult mouse hippocampus occur in a specific neurogenic niche, where a multitude of extracellular signaling molecules converges to regulate NSC proliferation as well as fate and functional integration. However, the underlying mechanisms how NSCs react to extrinsic signals and convert them to intracellular responses still remains elusive. NSCs contain a functional endocannabinoid system, including the cannabinoid type-1 receptor (CB1). To decipher whether CB1 regulates adult neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 90 publications
2
35
0
Order By: Relevance
“…Our findings do not necessarily undermine previous studies which have identified cell autonomous gene functions using stop-floxed reporters as a marker of target gene recombined cells (Zhou et al, 2018;Zimmermann et al, 2018;Franz et al, 2019;Zhang et al, 2019). Aside from the possibility that other reporter-target combinations show better recombination concordance than the two genes used in this study, if target gene recombination has a large cell-autonomous effect, it may still be detectable in models with suboptimal reporter-target recombination concordance due to the subpopulation of cells in which fluorescent protein presence is a true signal.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Our findings do not necessarily undermine previous studies which have identified cell autonomous gene functions using stop-floxed reporters as a marker of target gene recombined cells (Zhou et al, 2018;Zimmermann et al, 2018;Franz et al, 2019;Zhang et al, 2019). Aside from the possibility that other reporter-target combinations show better recombination concordance than the two genes used in this study, if target gene recombination has a large cell-autonomous effect, it may still be detectable in models with suboptimal reporter-target recombination concordance due to the subpopulation of cells in which fluorescent protein presence is a true signal.…”
Section: Discussionsupporting
confidence: 60%
“…In many studies, NSPC-targeted CreER T2 -lox systems are combined with a ubiquitously-expressed stop-floxed fluorescent reporter gene to confirm recombination in NSPCs (Sun et al, 2014;Kirby et al, 2015;Tannenholz et al, 2016). It is also common to use these fluorescent proteins more cell-specifically to investigate cell autonomous effects of recombination in the experimental gene of interest (Zimmermann et al, 2018;Zhou et al, 2018;Franz et al, 2019;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…CB1, CB2, and GPR55 take part in the regulation of neurogenesis. CB1 and GPR55 are crucial for proliferation and differentiation of neural stem cells (NSCs) [162][163][164]. Additionally, CB1 and CB2 control the development of astrocytes [165].…”
Section: Neurodegenerationmentioning
confidence: 99%
“…Observed actions of cannabis and endocannabinoids on proliferating neurons [ 27 , 28 ] may be less direct and, for example, may be transmitted through other molecules, cells, organs or the maternal organism. Potential actions of CB 1 R in later prenatal and postnatal proliferation zones such as the neocortical outer SVZ or hippocampal dentate gyrus [ 42 ] demands further investigation using methods with high cellular and subcellular resolution.…”
Section: Discussionmentioning
confidence: 99%